THE BORDERS BETWEEN AZERBAIJAN, GEORGIA, AND RUSSIA: SOVIET HERITAGE - ARKHIPOVA, Ekaterina (CENTRAL ASIA AND THE CAUCASUS, 2005)
The administrative-territorial reforms carried out under Soviet power in the Caucasus to delimitate Russia, Azerbaijan, and Georgia have always been and remain a bone of contention. So far their governments have not yet come to terms on several problems on certain border stretches. For fourteen years now, delimitation has been going on with varying intensity. Russia and Azerbaijan have come the closest to settling these disputes with respect to the Daghestanian stretch of their common border. The last talks about the debatable territories in the Khachmaz, Gusar, and Balakian districts of Azerbaijan were held in April 2005.1 Delimitation of the Russian-Georgian border is burdened with the uneasy relations between Tbilisi and the break-away republics of Abkhazia and South Ossetia. The budding advance toward a settlement was cut short by the military actions undertaken by Mikhail Saakashvili’s cabinet. Continued delimitation of 13 percent of the Russian-Georgian border is rigidly associated with the restoration of Georgia’s territorial integrity. So far, there is no clearly delimitated border between Georgia and Azerbaijan. Chairman of the Border Guard Department of Georgia Lieutenant-General B. Bitsadze offered the following comment on the closed meeting with the Azeri delegation held on 7 July 2005: “We have an administrative border, but we still do not know where the state border runs.”